Recent Advances in Peptide-Based Approaches for Cancer Treatment - Conibear, Anne C.; Schmid, Alanca; Kamalov, Meder; Becker, Christian F.W.; Bello, Claudia (Current Medicinal Chemistry, 2020)
Background: Peptide-based pharmaceuticals have recently experienced a renaissance due to their ability to fill the gap between the two main classes of available drugs, small molecules and biologics. Peptides combine the high potency and selectivity typical of large proteins with some of the characteristic advantages of small molecules such as synthetic accessibility, stability and the potential of oral bioavailability. Methods: In the present manuscript we review the recent literature on selected peptide-based approaches for cancer treatment, emphasizing recent advances, advantages and challenges of each strategy. Results: One of the applications in which peptide-based approaches have grown rapidly is cancer therapy, with a focus on new and established targets. We describe, with selected examples, some of the novel peptide-based methods for cancer treatment that have been developed in the last few years, ranging from naturally-occurring and modified peptides to peptidedrug conjugates, peptide nanomaterials and peptide-based vaccines. Conclusion: This review brings out the emerging role of peptide-based strategies in oncology research, critically analyzing the advantages and limitations of these approaches and the potential for their development as effective anti-cancer therapies.
Keywords: tumor targeting